Relationships between lead absorption and peripheral nerve conduction velocities in lead workers. - Araki, Shunichi; Honma, Tetsuo (Scandinavian Journal of Work, Environment & Health, 1976)
The motor sensory, and mixed nerve conduction velocities of median and posterior tibial nerves were measured in 39 lead workers whose blood lead (PbB) concentrations ranged from 2 to 73 µg/100 g with anaverage of 29 µg/100 g. The PbB concentrations significantly correlated with the maximal motor nerve conduction velocities (MCV) and mixed nerve conduction velocities (MNCV) of the median nerve in the forearm and with the MCV of the posterior tibial nerve. Erythrocyte delta-aminolevulinic acid dehydratase (ALAD) activity correlated similarly with the MCV and MNCV of the median nerve in the forearm, and the 24-hour urinary lead excretion following the intravenous administration of CaEDTA (20 mg/kg) (lead mobilization test) correlated with the MNCV. But no parameter correlated with the sensory nerve conduction velocities. By multiple regression analysis, a combination of the three parameters of lead absorption was found to correlate significantly with the MCV and MNCV of the median nerve in the forearm. The MCVs of the median and posterior tibial nerves in lead workers were significantly delayed in the PbB range of 29-73 µg/100 g (mean 45), in the lead mobilization test range from 173 to 3,540 µg/day (mean 973), and the ALAD activity range from 4.4 to 19.4 u. (mean 14.0), respectively.
Keywords: conduction velocity; delta-aminolevulinic acid dehydratase; dose-response relationship; lead; lead absorption; lead mobilization; lead mobilization test; lead mobilization test (with CaEDTA); lead worker; multivariate analysis; nerve conduction; peripheral nerve; peripheral nerve conduction velocity; subclinical neuropahty; worker